Experimental and numerical investigation of bolt-free preloaded connection for steel-framed modular buildings - Lee, Keunwoo; Cho, Bong Ho; Rasmussen, Kim J.R.; Jung, Dami (Journal of Constructional Steel Research, 2024)
This paper introduces an innovative bolt-free preloaded inter-module connection for steel-framed modular buildings, referred to as the ‘AJ’ connection. It provides the vertical connection between columns by engaging a preload induced by long steel rod bolts (SRB) and specially designed couplers. The preload is applied using a torque or impact wrench. Consequently, the connection simplifies the on-site assembly and disassembly processes of the modular building, thereby enhancing both construction speed and reusability of modules. In this study, the structural performance of the AJ connection was investigated experimentally and numerically. First, the coupler was tested under a uniaxial tensile load to check its strength. Then, preloading tests on assemblies of a coupler and a 3m long SRB were conducted to determine the torque-preload relationship. Subsequently, full-scale beam-to-column joints featuring the AJ connection were tested under monotonic loading to investigate its lateral-force resisting mechanism. Lastly, the seismic performance of the AJ connection was investigated using FE joint models calibrated against a combination of test results and geometric and material nonlinear analyses with imperfections (GMNIA). A comparative analysis with a welded connection was also conducted to evaluate the seismic performance of the AJ connection. The findings indicated that the AJ connection demonstrates seismic performance comparable to the welded connection, exhibiting Strong column-Weak beam behaviour for seismic moment-resisting frames. Additionally, it satisfies the ductility requirements for structures of ductility class DCM as specified by EN 1998–1.
Keywords: Experimental investigations; Inter-module; Inter-module connection; Modular buildings; Modular steel building; Modulars; Numerical investigations; Preloaded connection; Seismic Performance; Steel buildings; Experimental investigation; Inter-module connection; Modular steel building; Numerical investigation; Preloaded connection; Seismic performance